Chemical profile and potential antifungal of essential oil Schinus terebinthifolius and its by-products (Research, Society and Development, 2020)
This study aimed to investigate the distillation time to obtain a higher yield of essential oil and by-product (extract and hydrolate) of Schinus terebinthifolius seeds, to determine the main chemical constituents of these products and the potential fungitoxic on the Colletotrichum gloeosporioides. To obtain the essential oil and by-products, we used the method of steam distillation for 2.5, 4.0, 5.5 and 7.0 hours. The determination of the chemical composition was made by GC/MS. To determine the potential fungitoxic on mycelial growth of C. gloeosporioides various concentrations of the oil and by-products were tested. Distillation periods did not influence the yield of aqueous extract and essential oil hydrolate. No chemical compounds have been identified in hydrolat or aqueous extract with the use of GC analysis. The essential oil at concentrations of 2%, 3% and 4% inhibited approximately 47% of the in vitro development of the fungus C. gloeosporioides.